Author Correction: Cellular deconvolution of GTEx tissues powers discovery of disease and cell-type associated regulatory variants - Margaret K. R. Donovan (Nature Portfolio, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.